MODELING THE INFLUENCE OF RIVER FLOW AND SALINITY INTRUSION IN THE MEKONG RIVER ESTUARY, VIETNAM - Doan Quang Tri; Nguyen Cao Don; Pawan Kumar Mishra (International Association of Lowland Technology, 2014)
In this study, a hydrodynamic and solute transport model was applied to evaluate the effect of dredging on salinity intrusion in the estuary of the Mekong River, southern Vietnam. The model was calibrated and validated with available hydrographic measured data in 2000, 2004 and 2009. The flow and salinity at different positions in the river were dynamically assessed using the hydrodynamic and advection dispersion models. The factors of velocity, flow, water level providing flow boundary parameter for two-dimension model were calculated for both dry and flood season, while salinity was calculated only for the dry season to evaluate the impact of dredging to salinity intrusion process. The results of salinity intrusion simulation for 15 days show that the impact of dredging only occurs in the Quan Chanh Bo channel and does not affect the large river system. The minimum and maximum salinity concentrations along Quan Chanh Bo channel were predicted to be in the range of 2.0-6.0PSU.